Minority carrier barrier heterojunctions for improved thermoelectric efficiency. (March 2015) - Burke, Peter G.; Curtin, Benjamin M.; Bowers, John E.; Gossard, Arthur C.
Abstract: We propose and demonstrate the beneficial use of minority carrier blocking layers to lessen bipolar conduction at elevated temperatures and increase the Seebeck coefficient in a thermoelectric material. Bipolar conduction, caused by thermally activated intrinsic carriers in semiconductors, causes a detrimental "roll-over" in the Seebeck coefficient and increase in thermal conductivity, measured as a function of temperature. We propose that these negative effects can be lessened or delayed in a small band gap host matrix by incorporating wider band gap semiconductor layers to impede the thermal diffusion of minority carriers over majority carriers. To prove this concept, a composite material grown by molecular beam epitaxy of p-type InAs layers and electron blocking p-type AlSb layers were grown and measured. We show improved thermoelectric properties over just p-type InAs in measurements from 110 K to 600 K. Graphical abstract: Highlights: Conception of novel idea for improving thermoelectric efficiency in semiconductors. Bipolar conductivity is reduced in MBE-grown composite heterojunctions. Heterojunctions are used to reduce negative contribution of thermally activated carriers. >2x increase in power factor of InAs/AlSb composites utilizing electron-blocking layers.